2005
DOI: 10.3748/wjg.v11.i13.1951
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of low dose of melatonin against cholestatic oxidative stress after common bile duct ligation in rats

Abstract: AIM:To investigate the role of oxidative injury and the effect of exogenous melatonin administration on liver damage induced by bile duct ligation (BDL), and second, to evaluate the role of nitric oxide (NO), a free oxygen radical, in oxidative injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
5
41
0
1
Order By: Relevance
“…GSH is a key intracellular antioxidant that is capable of interacting with free radicals to repair membrane lipid peroxides. Our data showed BDL-induced cholestasis in developing rat is characterized by accumulation of ROS in the liver is associated with reduced GSH/GSSG ratios, which is in line with adult BDL-induced cholestatic rat (1,4,25,26,33). A relative decrease of GSH and an increase of GSSG in the liver, although both GSH and GSSG levels decrease in plasma, have been reported in adult BDL rats (33).…”
Section: Discussionsupporting
confidence: 61%
“…GSH is a key intracellular antioxidant that is capable of interacting with free radicals to repair membrane lipid peroxides. Our data showed BDL-induced cholestasis in developing rat is characterized by accumulation of ROS in the liver is associated with reduced GSH/GSSG ratios, which is in line with adult BDL-induced cholestatic rat (1,4,25,26,33). A relative decrease of GSH and an increase of GSSG in the liver, although both GSH and GSSG levels decrease in plasma, have been reported in adult BDL rats (33).…”
Section: Discussionsupporting
confidence: 61%
“…Recent evidence has shown that melatonin has protective effects on liver and hepatic injury after extrahepatic bile duct ligation in rats (Shiesh et al, 2000;Esrefoglu et al, 2005;Ohta et al, 2005). In addition to liver and hepatic damage, free radical accumulation associated with bile duct ligation has been implicated in the genesis of gallstone (Eder et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…18 Also reported was a protective effect of Mel against cholestatic oxidative stress, induced by common bile duct ligation in Sprague-Dawley rats. 19 It is worth recalling that Mel can also exert other protective effects against pathological processes occurring as a result of AFB1 administration. Meki et al 20 showed that co-administration of AFB1 (by gastric galvage) and Mel (given either orally or in the form of microcapsules) reduced the apoptotic rate, which was increased by AFB1 alone, in liver tissue.…”
Section: Introductionmentioning
confidence: 99%